Collaboration Between School Counselors and Early Childhood Teachers in Strengthening the Character Values of the Indonesian Children’s Great Habits Program - Martin Martin; Riki Maulana; Ema Sukmawati; Martin Martin; Riki Maulana (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The Government of the Republic of Indonesia, through its Indonesia Gold 2045 vision, emphasizes the strengthening of character-based human resources. One of the implementations is carried out through the Seven Habits of Great Indonesian Children program. This study aims to describe the collaboration between classroom teachers and school counselor in strengthening “Indonesian Children’s Great Habits” character values at the kindergarten. The study uses a descriptive qualitative approach with a descriptive study design. The results of the study show that the development of “Indonesian Children’s Great Habits” character values is in the category of Developing as Expected, covering religious values, discipline, responsibility, cooperation, social awareness, manners, self-control, empathy, and independence. The collaboration between classroom teachers and school counselors was carried out through the stages of planning, implementation, monitoring, and evaluation. Factors supporting collaboration included teachers' commitment to character education, open communication between school members and parents, school policies, and a conducive school culture. The obstacles encountered include limited time for collaboration, differences in understanding of roles, and variations in parental support. Efforts to overcome these obstacles are carried out through collaboration scheduling, strengthening understanding of roles, and improving communication and parental involvement in character building for children.